Effects of emotional expression and implied causal agency on leadership perception and responsibility attribution in an Asian context. - Lim, Huiying. (2008)
Our study reflects the effect of emotions and implied causal agency on leadership perception and responsibility attribution in an collectivist Asian culture. We proposed that sadness and group agency are conversely valued. For collective responsibility and causality to group dispositions, we proposed that sadness and group agencies cause higher level of collective responsibility.